Evaluation of MAA Analogues as Potential Candidates to Increase Photostability in Sunscreen Formulations - Jacobo Soilán; Leonardo López-Cóndor; Beatriz Peñín; José Aguilera; María Victoria de Gálvez; Diego Sampedro; Raúl Losantos (Photochem, 2024)
Avobenzone is one of the most widely used sunscreens in skin care formulations, but suffers from some drawbacks, including photo instability. To mitigate this critical issue, the use of octocrylene as a stabilizer is a common approach in these products. However, octocrylene has been recently demonstrated to show potential phototoxicity. The aim of this work is to analyze the performance of a series of mycosporine-like amino acid (MAA)-inspired compounds to act as avobenzone stabilizers as an alternative to octocrylene. Different avobenzone/MAA analogue combinations included in galenic formulations were followed under increasing doses of solar-simulated UV radiation. Some of the synthetic MAA analogues analyzed were able to increase by up to two times the UV dose required for 50% of avobenzone photobleaching. We propose some of these MAA analogues as new candidates to act as avobenzone-stabilizing compounds in addition to their UV absorbance and antioxidant properties, together with a facile synthesis.